The vertebrate fauna from the “stipite” layers of the Grands Causses (Middle Jurassic, France) - Knoll, Fabien; López-Antoñanzas, Raquel (Frontiers in Ecology and Evolution, 2014)
The “stipites” are Bathonian (Middle Jurassic) coals that formed in an everglades-like environment and are now exposed in the Grands Causses (southern France). The vertebrate assemblage of the “stipites” and of the transitional layers to the carbonates in which they are interspersed are reviewed. To date, only small-sized and isolated vertebrate bones, teeth, and scales have been recovered. These record the presence of sharks (Hybodus, Asteracanthus), bony fishes (Lepidotes, Pycnodontiformes, Caturus, Aspidorhynchus), amphibians (Anura, Albanerpetontidae), and reptiles (Crocodylomorpha, Ornithischia, Theropoda). Despite its relatively limited taxonomic diversity, the vertebrate assemblage from the “stipites” and from their associated layers is notable for being one of the few of this age with both terrestrial and marine influences. Compared to other approximately coeval formations in Western Europe, the “stipites” vertebrate assemblage is surpassed in diversity only by those from the British Isles.